2021
DOI: 10.1038/s41598-021-85951-7
|View full text |Cite
|
Sign up to set email alerts
|

Single dose of a replication-defective vaccinia virus expressing Zika virus-like particles is protective in mice

Abstract: Zika virus (ZIKV), a flavivirus transmitted primarily by infected mosquitos, can cause neurological symptoms such as Guillian–Barré syndrome and microcephaly. We developed several vaccinia virus (VACV) vaccine candidates for ZIKV based on replication-inducible VACVs (vINDs) expressing ZIKV pre-membrane (prM) and envelope (E) proteins (vIND-ZIKVs). These vIND-ZIKVs contain elements of the tetracycline operon and replicate only in the presence of tetracyclines. The pool of vaccine candidates was narrowed to one … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 41 publications
(27 reference statements)
0
6
0
Order By: Relevance
“…The JEV prM protein signal peptide was also previously used with the VLPs of dengue virus ( 33 ). Moreover, substituting one amino acid in the prM signal sequence of ZIKV led to enhanced secretion of E protein, which was even higher than the protein level obtained with the use of the JEV signal peptide ( 16 ). In the case of the P2A peptide, this is the first report that used P2A in the flavivirus VLPs construct.…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…The JEV prM protein signal peptide was also previously used with the VLPs of dengue virus ( 33 ). Moreover, substituting one amino acid in the prM signal sequence of ZIKV led to enhanced secretion of E protein, which was even higher than the protein level obtained with the use of the JEV signal peptide ( 16 ). In the case of the P2A peptide, this is the first report that used P2A in the flavivirus VLPs construct.…”
Section: Discussionmentioning
confidence: 82%
“…Naturally, two envelope glycoproteins of ZIKV, prM and E, are able to assemble into VLPs and are further secreted to the cell culture medium when expressed together in eukaryotic cells ( 14 ). However, the level of VLPs secretion may be low, and therefore different strategies, such as exchanging the signal sequence of prM protein or the transmembrane domains of E protein to analogous regions of Japanese encephalitis virus (JEV), have been used ( 15 , 16 ). Additionally, capsid protein (C) may be added to the VLPs construct to facilitate production; however, this strategy requires coexpression with viral protease to cleave the C protein from prM and E proteins.…”
Section: Introductionmentioning
confidence: 99%
“…No plaque-forming virions could be recovered from ovaries of mice infected intraperitoneally with viP11A6L without DOX, while a significantly higher level of viral load was detected with DOX supplied in drinking water, to a level indistinguishable from WT VACV-infected mice. Another study adapting this strategy was published by the same group to confirm the feasibility of using a replication-inducible VACV as a vaccine vector for Zika virus (vIND-ZIKV) [ 50 ]. The vaccine did not lead to any weight loss or clinical signs in intranasally infected CB6F1 mice in the absence of DOX, indicating a consistent safety profile.…”
Section: Enhanced Safety Mechanismsmentioning
confidence: 99%
“…Interestingly, it has recently been shown that tetracycline-inducible vaccinia expressing prM and E protein induced high anti-E IgG titers in vitro; on the other hand, in vivo, mice treated with anti-IFNAR1 and vaccinated with a single dose were protected from ZIKV, with an increase of interferon-gamma (IFN-γ)-secreting splenocytes and the induction of a humoral response [80].…”
Section: Zikv and The Host Immune Responsesmentioning
confidence: 99%